Alcohol use among adolescents in India: a systematic review. (7th January 2022) - Nadkarni, Abhijit; Tu, Allison; Garg, Ankur; Gupta, Devika; Gupta, Sonal; Bhatia, Urvita; Tiwari, Niharika; Heath, Anna; Wen, Karen; Fernandes, Godwin; Velleman, Richard
Abstract: Background: Alcohol use is typically established during adolescence and initiation of use at a young age poses risks for short- and long-term health and social outcomes. However, there is limited understanding of the onset, progression and impact of alcohol use among adolescents in India. The aim of this review is to synthesise the evidence about prevalence, patterns and correlates of alcohol use and alcohol use disorders in adolescents from India. Methods: Systematic review was conducted using relevant online databases, grey literature and unpublished data/outcomes from subject experts. Inclusion and exclusion criteria were developed and applied to screening rounds. Titles and abstracts were screened by two independent reviewers for eligibility, and then full texts were assessed for inclusion. Narrative synthesis of the eligible studies was conducted. Results: Fifty-five peer-reviewed papers and one report were eligible for inclusion in this review. Prevalence of ever or lifetime alcohol consumption ranged from 3.9% to 69.8%; and prevalence of alcohol consumption at least once in the past year ranged from 10.6% to 32.9%. The mean age for initiation of drinking ranged from 14.4 to 18.3 years. Some correlates associated with alcohol consumption included being male, older age, academic difficulties, parental use of alcohol or tobacco, non-contact sexual abuse and perpetuation of violence. Conclusion: The evidence base for alcohol use among adolescents in India needs a deeper exploration. Despite gaps in the evidence base, this synthesis provides a reasonable understanding of alcohol use among adolescents in India and can provide direction to policymakers.